Tongbixiao Pills Improve Gout by Reducing Uric Acid Levels and Inhibiting Inflammation - Shijun Xi; ZhiguoShao; Lu Li; Zhuang Gui; Peng Liu; Qi Jiang; Yuan Yu; Wen Zhou; Ziqi Zhou; Shuo Zhang; Xiao Chun Peng; Bo Su (SAGE Publishing, 2022)
Gout is a chronic disease. Gout symptoms are often experienced in the middle of the night. The onset of gout in the middle of the night is closely related to abnormal liver and gallbladder meridian. The purpose of this study was to investigate the clinical efficacy and possible mechanism of action of Tongbixiao pills in the treatment of hyperuricemia and gouty arthritis. The Tongbixiao pills we used included several traditional Chinese medicines, most of which tonify the spleen; strengthen the liver; benefit the kidney; and reduce heat, dampness, and blood stasis. In this randomized clinical study of 105 patients, we found that Tongbixiao pills can reduce uric acid levels in hyperuricemia patients. Additionally, the efficacy was similar to that of allopurinol and the level of uric acid did not increase significantly at eight weeks after withdrawal. In the absence of notable adverse reactions, Tongbixiao pills can also increase uric acid excretion, reduce serum creatinine and lipid levels, and reduce inflammation and relieve gout symptoms. In addition, we used SD rats to simulate gout and arthritis and divided them into five groups: normal group, model group, low-dose group, medium-dose group, and high-dose group. The inflammatory indices of the 40 SD rats were observed. After seven days, ankle swelling in rats in the treatment group was significantly reduced. The indices of uric acid, creatinine, and urea nitrogen in the treatment group were significantly lower than those in the model group, which proved that Tongbixiao pills could inhibit hyperuricemia in rats, thus treating gout. This study demonstrates that Tongbixiao pills can treat gout, provide more treatment options for gouty arthritis, and improve the quality of life of patients.